Macroeconomic effects of ownership structure in OECD countries - Donatella Gatti (Institute for the Study of Labor (IZA), 2008)
The paper investigates the impact of ownership concentration on GDP growth, for a sample of 18 OECD countries over the period 1980 to 2004. The econometric analysis shows that more concentrated ownership can speed up growth, for countries approaching the technological frontier, provided that labour market regulation is sufficiently tight. In the absence of employment regulation, the logic of financial markets discipline applies and dispersed ownership appears as more favorable for growth. Based on econometric results, impact coefficients are calculated allowing to evaluate the growth points gained/lost following a given change in ownership concentration. This exercise reveals that a reform in the domain of ownership structure can yield sizeable effects in terms of growth. Importantly, these effects are unequally distributed across countries: Anglo-Saxon countries would take more advantage of deregulation (i.e. increased dispersion of ownership in a context of deregulated labour markets) while continental European countries would benefit more from increased concentration of ownership in a context of reinforced labour regulation.
urn:nbn:de:101:1-2008032642
Keywords: O43; 330; Ownership concentration; labour market regulation; growth; developed countries; Eigentümerstruktur; Wirtschaftskonzentration; Wirtschaftswachstum; Arbeitsmarktflexibilisierung; OECD-Staaten